Analysis of labor supply and labor demand in Türkiye with SVAR models - Özek, Yavuz; Koşaroğlu, Şerife Merve (My University, 2025)
The main objective of sustainable economic growth policy is to achieve full employment in the labor market. While classical economic theory considers labor supply and demand as a function of the real wage, Keynesian economics argues that only labor demand is a function of the real wage. Therefore, determining the factors affecting labor supply and demand in emerging economies will help to formulate policies for the labor market. In this study, labor supply and demand functions in the Turkish economy are estimated with structural vector autoregression models using annual data for the period 1990-2022. According to the results of the empirical analysis, it is found that the minimum wage level is effective in labor demand, but average minimum real wages are not effective on labor supply. In the labor demand function, the views of Classical economics and Keynesian economics on the labor market are valid in the labor supply function. In line with these results, it is concluded that labor productivity is high in the Turkish economy, but real wages do not contribute to economic growth through aggregate demand and employment growth due to the institutional structure in the labor market.
Keywords: Labor Supply; Structural VAR; Labor Demand